An Analytical Study Of Total Harmonics Reduction In APF Using Adaptive Zero Crossing Detection Techniques - Thajeel, Ekhlas Mhawi; Hamdan, Daniyal; M. H., Sulaiman; Mazin Mustafa, Mahdi (IJESRT, 2016)
The excessive waveform distortions in the present power distribution systems are produced mainly by the large number of non-linear loads. Such distributed sources of harmonics cannot be easily treated by the traditional mitigation methods. Furthermore, classical control theory suffers from some limitations due to the nature of the controlled system. These problems can be overcome by using adaptive zero crossing detection (AZCD). A comparison between the conventional PI controller and AZCD for three-phase, six-switch VSI-based APF using synchronous reference frame (SRF) theory is realized in this paper to improve the step transient response of DC link voltage of APF at sudden change of the load. Shunt active power filters operate as a controllable current source and are implemented preferable with voltage source PWM inverters, with a dc capacitor. The time domain simulation is performed using MATLAB/ Simulink environment to compensate the non-active power in different conditions. Results showed that the source current THD % can be reduced to less than 5% the harmonic limit imposed by the IEEE-519 standard and the DC voltage are settled to their steady state values within a few cycles. It is clear from the results that DC link with AZCD has better dynamic behavior than conventional PI control strategy.